MENINGKATKAN PERKEMBANGAN KOGNITIF MENGGUNAKAN MEDIA GAMBAR PADA KELOMPOK A DI RA AT THAYYIBAH BALONGDOWO CANDI SIDOARJO - Anik Anik; Muhammad Hanif; Rosichin Mansur (Jurnal Dewantara, 2020)
The purpose of research is to improve and enhance learning practices and to help teachers and other education personnel in overcoming learning problems at RA At Thayyibah. Cognitive development is that children have the ability to design, remember and find solutions to problems encountered. At the age of 0-2 children begin to be able to distinguish things that are observed. It is a classroom action research. Data collection methods using interviews, observation, and documentation. Data analysis techniques use data reduction, data presentation, and drawing conclusions. Conclusions from the results of this study: (1) Describe activities using image media to improve cognitive development of children in group A in RA At thayyibah (2) Increase in cognitive development through the percentage of children with children being able to use media images in cycle 1 with the number of percentages 50%, then using picture media in group A children can be said to have increased, whereas in cycle 2 the percentage of children's cognitive ability increases to 80%, and children's ability to use image media has increased which is quite satisfying